Impact of age, follicle stimulating hormone and Johnsen's score on successful sperm retrieval by microdissection testicular sperm extraction - TSUJIMURA, AKIRA (Reprod Med Biol, 2005)
Background:  The spermatozoa retrieval rate achieved by microdissection testicular sperm extraction (TESE) for patients with non‐obstructive azoospermia is still approximately 50%, despite technical advances. Predicting a successful outcome is important to avoid unnecessary surgery. A study was conducted to determine a method for calculating the predicted probability of successful microdissection TESE. Methods:  Testicular spermatozoa were retrieved in 41 of 100 patients by microdissection TESE. Ten clinical factors were examined in the search for an optimal logistic model for predicting a good outcome. Once the best delimiting value was established, sensitivity and specificity were calculated. Results:  Patient age, serum follicle stimulating hormone (FSH) concentration and Johnsen's score (JS) were shown to be influential factors by multivariate logistic analysis. The mathematical model for predicting the probability of a successful outcome was as follows: P = (1 + exp[0.144 × patient age − 0.059 × serum FSH concentration − 1.310 × JS])(−1). When a predictive probability of 49.7% was selected as the best cut‐off value, sensitivity and specificity were 78.0% and 76.3%, respectively. Conclusion:  This present model is very useful for predicting successful microdissection TESE. In addition, we suggest that a younger patient age would increase the probability of success with this procedure. (Reprod Med Biol 2005; 4: 53–57)